2014
DOI: 10.1111/obr.12197
|View full text |Cite
|
Sign up to set email alerts
|

A new model of the role of psychological and emotional distress in promoting obesity: conceptual review with implications for treatment and prevention

Abstract: The lack of significant treatment and prevention progress highlights the need for a more expanded strategy. Given the robust association between socioeconomic factors and obesity, combined with new insights into how socioeconomic disadvantage affects both behaviour and biology, a new causal model is proposed. The model posits that psychological and emotional distress is a fundamental link between socioeconomic disadvantage and weight gain. At particular risk are children growing up in a disharmonious family en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
184
0
14

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(208 citation statements)
references
References 126 publications
(161 reference statements)
10
184
0
14
Order By: Relevance
“…In addition, obesity signifies non-adaptive coping strategies and the regulation of emotional state through food [54]. There is a high probability that due to strong stigmatization and alienation, individuals with obesity are faced with negative emotions and cope by engaging in (emotional) eating [55][56][57][58].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, obesity signifies non-adaptive coping strategies and the regulation of emotional state through food [54]. There is a high probability that due to strong stigmatization and alienation, individuals with obesity are faced with negative emotions and cope by engaging in (emotional) eating [55][56][57][58].…”
Section: Discussionmentioning
confidence: 99%
“…One possibility is that impoverished standard rodent cage environments model low socioeconomic status (Milgram et al, 2006). It has long been thought that socioeconomic status contributes to mental health, with higher prevalence of depression, anxiety, and schizophrenia in lower-income populations (Hemmingsson, 2014;Holzer et al, 1986;Kessler et al, 1994;Zimmerman and Katon, 2005). The specific environmental features responsible for the risk are difficult to delineate, however.…”
Section: Effects Of Rewarding Experiences On Adult Neurogenesis and Mmentioning
confidence: 99%
“…The potential role of psychological and emotional distress in obesity development has been less extensively researched (3) , but a generally positive relationship was found between negative affect or stress in children and weight gain (see Table 1) . This is particularly relevant because mental disorders affect 10-20 % of children and adolescents worldwide (28) and 47·7 % of the children in a European study presented psychosomatic or emotional symptoms (29) .…”
Section: Introductionmentioning
confidence: 99%
“…First, it has been assumed that the associations between stress and obesity share genetic factors like polymorphism on the serotonin 5-HT 2C receptor gene, monoamine oxidase A, serotonin transporter gene or the fat mass and obesity associated gene (FTO gene) (160)(161)(162) . In addition, a recent review suggested that socio-economic disadvantages and family disharmony are a common starting point for weight gain and psychological distress in children (3) . At the same time, several prenatal, perinatal and postnatal factors (for example, toxics exposure, maternal nutrition, maternal stress, maternal psychopathology and negative events during early life) have been identified as obesity and/or neurodevelopmental risk factors (161,163,164) .…”
Section: Limitations In the Interpretation Of The Modelmentioning
confidence: 99%